Urban Projections : a cinema and film centre for the Cape Town east city - McDonald, Ross (School of Architecture, Planning and Geomatics, 2016)
This thesis is concerned with the particular way in which people perceive urban space around them. It is my position that, further to the requirements of making buildings and urban spaces that are functional and comfortable, architects have the responsibility to engage the users of their designs on deeper levels. This deeper response to one's urban environment is a characteristic that good architecture always has. Architecture that is invested with a strong sense of meaning, through the specificities of its experiential and formal qualities and with other associations it may possess (historical, cultural, etc.) plays an important role in shaping the everyday urban realities of people in the city. This document serves to present the theoretical research and outline the approach to design that I have followed, regarding my thesis design project. Both my theory of architecture and theory of technology papers have been included in this document in their entirety, as they are both frames through which I have approached the design process. Interspersed are additional sections of text and diagrammes that outline the specifics of the design project I have undertaken subsequent to (and resulting from) the initial theoretical research.